ALUMINISATION THERMOCHEMICAL TREATMENT APPLIED TO WEAR RESISTANT COATINGS - CIOFU Florin; STĂNCIOIU Alin (Fiabilitate şi Durabilitate)
Aluminisation process is particularly widespread the process to increase wear resistance, oxidation resistance, heat-resistant alloysto replace expensive heat resistant to 800oC-1000oC, with cheaper materials